La planificación de bibliotecas públicas en España de 1978 a la actualidad - Menéndez Seoane, Susana (Revista General de Información y Documentación, 2008)
This article will present a brief way about the actions that Spanish Government have developed about planning public libraries since the Constitution of 1978 comes into effect. For this we will take as starting the changes made in the Spanish Libraries System by this Constitution and posterior legislation and in any case the management of the public libraries could be affected. This analysis will be useful to concentrate in the different initiatives that about planning libraries have developed from Department of Culture. We have emphasized the current initiatives to deduce if a national library system or a information policy really exists or not.
Keywords: Public libraries; Planning; National Information System; Information Policy